Hyundai EV Battery Plant In South Korea-Indonesia Bilateral Cooperation - Tamara Pinka Theresia; Nurfarah Nidatya (Universitas Airlangga, 2026)
South Korea’s New Southern Policy (NSP), seeks to diversify economic partnerships beyond China and the United States by strengthening ties with Southeast Asia. Indonesia became a pivotal partner through the Indonesia–Korea Comprehensive Economic Partnership Agreement (IK-CEPA). Within this framework, Hyundai’s EV Battery Plant in Karawang represents a flagship investment advancing the prosperity pillar of NSP. This study investigates how South Korea and Indonesia address challenges in implementing the prosperity principle of NSP through IK-CEPA, focusing on Hyundai’s EV Battery Plant during 2023–2025. Guided by Complex Interdependence Theory and the CEPA concept, the research analyzes the interdependent relationship between the two countries in overcoming obstacles within strategic economic cooperation. A qualitative descriptive approach was employed, supported by a literature review and limited interviews, analyzed using the Miles & Huberman model. Revealing two main obstacles: Indonesia’s regulatory complexity, including overlapping institutional authority and licensing delays, and global EV market volatility, such as nickel price fluctuations and the EV chasm. To address these challenges, both countries pursued cross-ministerial coordination, joint operational checks, and active involvement in KADIN and KOCHAM. These efforts underscore that prosperity is a dynamic process requiring continuous adaptation and collaboration, reinforcing complex interdependence in modern economic diplomacy. Keywords: NSP; IK-CEPA; Hyundai EV Battery Plant; FDI; Complex Interdependence.